v(v)+3v-18=0

Simple and best practice solution for v(v)+3v-18=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for v(v)+3v-18=0 equation:


Simplifying
v(v) + 3v + -18 = 0

Multiply v * v
v2 + 3v + -18 = 0

Reorder the terms:
-18 + 3v + v2 = 0

Solving
-18 + 3v + v2 = 0

Solving for variable 'v'.

Factor a trinomial.
(-6 + -1v)(3 + -1v) = 0

Subproblem 1

Set the factor '(-6 + -1v)' equal to zero and attempt to solve: Simplifying -6 + -1v = 0 Solving -6 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1v = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1v = 0 + 6 -1v = 0 + 6 Combine like terms: 0 + 6 = 6 -1v = 6 Divide each side by '-1'. v = -6 Simplifying v = -6

Subproblem 2

Set the factor '(3 + -1v)' equal to zero and attempt to solve: Simplifying 3 + -1v = 0 Solving 3 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1v = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1v = 0 + -3 -1v = 0 + -3 Combine like terms: 0 + -3 = -3 -1v = -3 Divide each side by '-1'. v = 3 Simplifying v = 3

Solution

v = {-6, 3}

See similar equations:

| 10(x-2)/5x-10 | | 3(4x+6)=9x+122 | | (5u-4)(3-u)=0 | | -6(c+1)-(6+5c)= | | (2x+3)+(4x+8)=180 | | =(y+6u)(7y-7u-5) | | -12x-20=-10x-15 | | -2x-10=3x-15 | | fn=5n+6 | | 16x-10+9=99-30x | | 6cosx+5=-5cosx+14 | | x+.05x=252000 | | (6x-5)(8x+3)=0 | | 187=-x+8 | | x+.05x=456 | | x+.05x=110 | | f(x)=x^3-6x^2-x+6 | | p^6-1=0 | | Y=-14x*-70x | | 2x/11 | | 3x+6x+2=-4x | | 10+10x=50+2x | | 8+w-4.7w-.5= | | 15x^2+26x+7= | | 125x^6-8=equation | | -4/9x=8 | | 5/√5xy^2 | | 5/√(5xy^2 | | 0=x^2+x-8 | | 80p^2r-245b^2r=0 | | 2v^2-10+12=0 | | 16v^4y^5-4v/4v^3x^6 |

Equations solver categories